A review on various methods to improve process capabilities of electrical discharge machining process. (2021) - Choubey, Mayank; Rawat, Manish
Abstract: The propensity to increase the machining performance of various electric discharge machining (EDM) processes is becoming more and more prominent by many researchers. The exploitation of vibration to the workpiece, tool, and dielectric fluid in various mediums like fluid and gas, the addition of additives to dielectric medium examined by the researchers. The results of the research show a significant improvement in the process in terms of enriched material removal rate (MRR), reduced tool wear, and quality finish. This research article reviews the application of vibration to the electrodes, dielectric medium, and the use of different additives in a dielectric medium in various EDM processes. The review of various vibration-assisted techniques, powder mixed EDM, and their impact on output performance parameters have been described. Literature suggested that the exploitation of vibration to the electrodes enhanced the output process parameters in terms of higher MRR, minimum tool wear, and superior surface quality due to optimum flushing performance of contaminants from the gap. The application of vibration also reduced the short-circuiting, increased discharge frequency, and stabilizes the machining process. The literature on adding additives in various EDM processes also reported a significant improvement in the machining performance by reduced short-circuiting thereby reducing insulating characteristics of the dielectric medium. Based on the review the research opportunities for researchers for further research have been identified to strengthen the capabilities and capacity of various EDM processes.